Prevalence and risk factors of measles seronegativity in a cohort of HIV‐positive subjects: a retrospective study - Dauby, N; Martin, C; Hainaut, M; Grammens, T; Van den Wijngaert, S; Delforge, M; De Wit, S (HIV medicine, 2018)
Objectives Measles infection is a vaccine‐preventable disease currently resurging in Europe. HIV‐infected subjects are at higher risk of complications following measles infection. We investigated the risk factors associated with being seronegative in a cohort of HIV‐infected subjects. Methods All HIV‐infected subjects in our cohort who had a measles serological test performed between December 2005 and May 2017 were retrospectively identified. A measles immunoglobulin G (IgG) titre > 275 mIU/mL was considered protective. Risk factors were analysed using logistic regression. Results Measles serology was available in 273 of 3124 subjects in active follow‐up (8.7%). The prevalence of measles seronegativity was 21.6% (59 of 273). In the univariate analysis, being born after 1970 and HIV infection by vertical transmission were both associated with a higher risk of measles seronegativity, while a nadir CD4 T‐cell count < 200 cells/μL was associated with a lower risk of measles seronegativity. In the multivariate analysis, only being born after 1970 [odds ratio (OR) 4.9; 95% confidence interval (CI) 1.3–18.7] and vertical transmission (OR 7.7; 95% CI 3.3–18.3) were significantly associated with seronegativity. Among the vertically infected subjects with measles‐mumps‐rubella (MMR) immunization documentation, the median number of doses of vaccine received before testing was 2 (range 1–3). Conclusions HIV‐infected subjects born after 1970 and vertically infected subjects should be screened for measles seropositivity.